Facile Carbon Fluoride/Sulfur Hybrid Cathode for High‐Rate Lithium Batteries. Issue 13 (2nd July 2019) - Peng, Sikan; Wang, Chen; Yan, Shaojiu; Wang, Nan; Wang, Jixian; Dai, Shenglong
Abstract: A win‐win design and application of carbon fluoride/sulfur (CFx /S) hybrid cathode is demonstrated successfully for both high‐rate primary lithium/carbon fluoride battery and secondary lithium sulfur (Li−S) battery for the first time. Ex situ X‐ray diffraction and Raman analyses are involved to shed light on the discharge mechanism of the CFx /S cathode. The maximum power density breaks through 32023 W kg −1 within the primary discharge by the low fluorine content CFx /S cathode. The high‐fluorine content one can retain an appreciable reversible capacity after 200 cycles at ultra‐fast rate of over 10 C. To the best of our knowledge, it is the first time investigating the effect of CFx as a sulfur carrier in Li−S batteries. This facile and effective strategy of CFx /S hybrid cathode opens a new avenue for high performance lithium batteries. Abstract : A win‐win design and application of carbon fluoride/sulfur hybrid cathode, facilely enables the Li/CFx and Li−S battery exhibiting excellent rate performances.